Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=\frac{1}{1\cdot2}+\frac{2}{2\cdot4}+\frac{3}{4\cdot7}+\frac{4}{7\cdot11}+...+\frac{10}{46\cdot56}\)
\(A=1-\frac{1}{2}+\frac{1}{2}-\frac{1}{4}+\frac{1}{4}-\frac{1}{7}+\frac{1}{7}-\frac{1}{11}+...+\frac{1}{46}-\frac{1}{56}\)
\(A=1-\frac{1}{56}\)
\(A=\frac{55}{56}\)
\(B=\frac{4}{3\cdot7}+\frac{4}{7\cdot11}+\frac{4}{11\cdot15}+...+\frac{4}{23\cdot27}\)
\(B=\frac{1}{3}-\frac{1}{7}+\frac{1}{7}-\frac{1}{11}+\frac{1}{11}-\frac{1}{15}+...+\frac{1}{23}-\frac{1}{27}\)
\(B=\frac{1}{3}-\frac{1}{27}\)
\(B=\frac{8}{27}\)
\(C=\frac{4}{3\cdot6}+\frac{4}{6\cdot9}+\frac{4}{9\cdot12}+...+\frac{4}{99\cdot102}\)
\(C=\frac{4}{3}\left(\frac{3}{3\cdot6}+\frac{3}{6\cdot9}+\frac{3}{9\cdot12}+...+\frac{3}{99\cdot102}\right)\)
\(C=\frac{4}{3}\left(\frac{1}{3}-\frac{1}{6}+\frac{1}{6}-\frac{1}{9}+\frac{1}{9}-\frac{1}{12}+...+\frac{1}{99}-\frac{1}{102}\right)\)
\(C=\frac{4}{3}\left(\frac{1}{3}-\frac{1}{102}\right)\)
\(C=\frac{4}{3}\cdot\frac{33}{102}\)
\(C=\frac{22}{51}\)
( 1+2+3+4-1-2-3-4) * 1*2*...........*8*9
= 0 * 1*2*...........*8*9
= 0
a) 5/9 + 4/9 . 3/7 + 4/9 . 4/7
= 5/9 + 4/9 . (3/7 + 4/7)
= 5/9 + 4/9 . 1
= 5/9 + 4/9
= 1
a) 1/2 + 3/4 - (3/4 - 4 - 5)
= 1/2 + 3/4 - 3/4 + 4 + 5
= (3/4 - 3/4) + (4 + 5) + 1/2
= 0 + 9 + 1/2
= 19/2
b) [9/16 + 8/(-27)] - (19/27- 7/16 - 2)
= 9/16 - 8/27 - 19/27 + 7/16 + 2
= (9/16 + 7/16) + (-8/27 - 19/27) + 2
= 1 - 1 + 2
= 2
c) -5/8 . [4/9 + 7/(-12)]
= -5/8 . (-5/36)
= 25/288
d) 7/10 . (-3/5) + 7/10 . (-2/5) - (-3/10)
= 7/10 . (-3/5 - 2/5) + 3/10
= 7/10 . (-1) + 3/10
= -2/5
e) -3/7 . 5/9 + 4/9 . (-3/7) + 2 3/7
= -3/7 . (5/9 + 4/9) + 17/7
= -3/7 . 1 + 17/7
= 2
f) 8 2/7 - (3 4/9 + 4 2/7)
= 8 + 2/7 - 3 - 4/9 - 4 - 2/7
= (8 - 3 - 4) + (2/7 - 2/7) - 4/9
= 1 - 4/9
= 5/9
h) 3.(-1/2)² - (4/5 + 8/15) : 5/6
= 3.1/4 - 4/3 : 5/6
= 3/4 - 8/5
= -17/20
a, -3/4 + 3/7 + -1/4 + 4/9 + 4/7
=\(\left(\frac{-3}{4}+\frac{-1}{4}\right)+\left(\frac{3}{7}+\frac{4}{7}\right)+\frac{4}{9}\)
=\(-1+1+\frac{4}{9}\)
=\(\frac{4}{9}\)
b, -7/9 x 4/11 + -7/9 x 7/11 + 5 và 7/9
\(=\frac{7}{9}x\frac{-4}{11}+\frac{7}{9}x\frac{-7}{11}+5x\frac{7}{9}\)
\(=\frac{7}{9}x\left(\frac{-4}{11}+\frac{-7}{11}+5\right)\)
\(=\frac{7}{9}x4\)
\(=\frac{28}{9}\)
c, ( 21/31 + 2013/6039 ) - ( 44/53 - 10/31) - /53
a/
$\frac{7}{4}+\frac{9}{16}=\frac{28}{16}+\frac{9}{16}=\frac{28+9}{16}=\frac{37}{16}$
b/
$\frac{-70}{27}+\frac{35}{9}=\frac{-70}{27}+\frac{105}{27}=\frac{35}{27}$
c/
$\frac{-4}{-5}+\frac{-2}{3}=\frac{4}{5}-\frac{2}{3}=\frac{12}{15}-\frac{10}{15}=\frac{2}{15}$
d/ Đề thiếu. Bạn xem lại.
i/
$\frac{-7}{2}+(\frac{-5}{-4}-\frac{4}{-9}$
$=\frac{-7}{2}+\frac{5}{4}+\frac{4}{9}$
$=\frac{-14}{4}+\frac{5}{4}+\frac{4}{9}$
$=\frac{-9}{4}+\frac{4}{9}=\frac{-81}{36}+\frac{16}{36}=\frac{-65}{36}$
k/
$\frac{1}{4}+\frac{1}{3}-\frac{1}{2}$
$=\frac{3}{12}+\frac{4}{12}-\frac{6}{12}=\frac{1}{12}$
m/
$\frac{-1}{9}-\frac{1}{7}-\frac{3}{4}$
$=-(\frac{1}{9}+\frac{1}{7}+\frac{3}{4})$
$=-(\frac{28}{252}+\frac{36}{252}+\frac{189}{252})$
$=\frac{-253}{252}$
n/
$\frac{11}{12}-(\frac{-3}{18}+\frac{5}{6}$
$=\frac{11}{12}+\frac{1}{6}+\frac{5}{6}$
$=\frac{11}{12}+1=\frac{23}{12}$
o/
$\frac{20}{17}+\frac{-11}{2}-\frac{30}{4}$
$=\frac{20}{17}-\frac{11}{2}-\frac{15}{2}$
$=\frac{20}{7}-13=\frac{-71}{7}$
v/
$\frac{1}{2}-\frac{3}{4}+\frac{5}{6}$
$=\frac{6}{12}-\frac{9}{12}+\frac{10}{12}$
$=\frac{6-9+10}{12}=\frac{7}{12}$
a, \(\left(4\dfrac{1}{9}+3\dfrac{1}{4}\right).2\dfrac{1}{4}+2\dfrac{3}{4}\)
\(=\left(\dfrac{37}{9}+\dfrac{13}{4}\right).\dfrac{9}{4}+\dfrac{11}{4}\)
\(=\dfrac{265}{36}.\dfrac{9}{4}+\dfrac{11}{4}\)
\(=\dfrac{265}{16}+\dfrac{11}{4}\)
\(=\dfrac{309}{16}\)
b, \(\dfrac{9}{23}.\dfrac{5}{8}+\dfrac{9}{23}.\dfrac{3}{8}-\dfrac{9}{23}\)
\(=\dfrac{45}{184}+\dfrac{27}{184}-\dfrac{9}{23}\)
\(=\dfrac{9}{23}-\dfrac{9}{23}\)
\(=\dfrac{1}{1}\)
c, \(1+\left(\dfrac{9}{10}-\dfrac{4}{5}\right)\div3\dfrac{1}{6}\)
\(=1+\left(\dfrac{9}{10}-\dfrac{4}{5}\right)\div\dfrac{19}{6}\)
\(=1+\dfrac{1}{10}\div\dfrac{19}{6}\)
\(=1+\dfrac{3}{95}\)
\(=1\dfrac{3}{95}\)
d, ???
\(-\dfrac{3}{4}+\dfrac{3}{7}-\dfrac{1}{4}+\dfrac{4}{9}+\dfrac{4}{9}\\ =\left(-\dfrac{3}{4}-\dfrac{1}{4}\right)+\left(\dfrac{4}{9}+\dfrac{4}{9}\right)+\dfrac{3}{7}\\ =-1+\dfrac{8}{9}+\dfrac{3}{7}\\ =\dfrac{20}{63}.\)